If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + -1(-10) = 22 Multiply -1 * -10 b + 10 = 22 Reorder the terms: 10 + b = 22 Solving 10 + b = 22 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + b = 22 + -10 Combine like terms: 10 + -10 = 0 0 + b = 22 + -10 b = 22 + -10 Combine like terms: 22 + -10 = 12 b = 12 Simplifying b = 12
| 7x+14=4x-40 | | 8-4+3x+2=35 | | -6k-(-7-6k)=-89 | | 20=5-x | | 3a-1=5a+9 | | 3b+16=5b+11-3b | | 1=8(6k+2)-3(6k+5) | | -7(v+2)+3v+7=5v+12 | | 4u-7=u+2(4+u) | | 5(2x-1)+x=-38 | | 0=4+v | | 105=7(3+m) | | 3x+1=7-7y | | 2(x+4)+x=-x+6-10+2x | | 144=-12(x+5)-1 | | 0.45x+0.05(18-x)=0.10(-31) | | 56=2-6m | | 4u-7=u+(4+u) | | -243=-9(10+x)-2 | | 69x-18-9x=11+60x-29 | | 27-3x=9 | | .25x-.05(4-x)=.10(-2) | | 7(6-(2*-37))=5((-3*-37)+1) | | 9+2r-1=9r+17-6r | | 5x+2=-1a | | x+13i=y-yi | | -4y+2-5=2y | | 2x-4(x-4)=-2+5x-3 | | 3(1-3x)-1=(-3x-2)-4x | | 3(3x-4)-16=6x-1 | | 3x+40+2x=90 | | 15z^2+14z+3= |